2015
DOI: 10.3354/meps11185
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of nereid polychaete size and density on sediment inorganic nitrogen cycling under varying oxygen conditions

Abstract: Chronic eutrophication and expanding seasonal hypoxia (O 2 < 63 µM) in estuaries like Chesapeake Bay have altered benthic faunal communities in favor of opportunistic species that can quickly populate organic-rich sediments following hypoxic events. It has been suggested that the biogenic activity of polychaetes can stimulate microbial ammonification, nitrification, and/or denitrification in estuarine sediments as well as increase the fluxes of inorganic nitrogen (NH 4 + , NO 2 − , NO 3 − , N 2 ) across the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Either way, these changes can be due to increased remineralisation rates and/or increased animal consumption of detritus. These results are similar to those of another study where a deposit-feeding polychaete worm was found to increase oxygenation and denitrification rates in sediments ex-situ, suggesting potential for nutrient remediation (Bosch et al, 2015). Moreover, we observed a stronger effect of worms in-situ than ex-situ, with organic content reduced up to 50% in-situ accompanied by increases in biodiversity at the location with medium levels of pollution.…”
Section: Introducing Below-ground Ecosystem Engineers Can Influence F...supporting
confidence: 91%
“…Either way, these changes can be due to increased remineralisation rates and/or increased animal consumption of detritus. These results are similar to those of another study where a deposit-feeding polychaete worm was found to increase oxygenation and denitrification rates in sediments ex-situ, suggesting potential for nutrient remediation (Bosch et al, 2015). Moreover, we observed a stronger effect of worms in-situ than ex-situ, with organic content reduced up to 50% in-situ accompanied by increases in biodiversity at the location with medium levels of pollution.…”
Section: Introducing Below-ground Ecosystem Engineers Can Influence F...supporting
confidence: 91%
“…In such environments there tends to be a predominance of small species with opportunistic reproductive modes that are able to respond quickly post-disturbance and can reach high abundances, but these species are more likely to have a low bioturbation potential (Solan et al 2004a;Queirós et al 2013). As per capita effects on sediment-water nutrient fluxes are disproportionately greater for larger polychaetes (Bosch et al 2015), there is less capacity for most of the resident infauna to influence biogeochemical processes. A similar effect is also true for non-cohesive sediments which, due to their inherent mobility, host a high proportion of opportunistic species (Collie et al 2000), but these communities also harbour large deep-burrowing fauna (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Deep burrowing macrofauna, during ventilation, pump N-and O 2 -rich bottom water downward (Nielsen et al 2004;Mermillod-Blondin and Rosenberg 2006;Renz and Foster 2013;Murphy and Reidenbach 2016). This stimulates microbial N-cycling pathways, including ammonification, nitrification and denitrification (Tuominen et al 1999;Bonaglia et al 2013;Stief 2013;Bosch et al 2015;Moraes et al 2018). Therefore, in macrofauna bioturbated sediments, the abundance and the activity of microbial communities often exceed those of surrounding, non-bioturbated sediments (Gilbertson et al 2012;Laverock et al 2014;Yazdani Foshtomi et al 2018;Samuiloviene et al 2019).…”
Section: Introductionmentioning
confidence: 99%